How has the rural digital economy influenced agricultural carbon emissions? Agricultural green technology change as a mediated variable - Zhang, Hongsheng; Guo, Kaitong; Liu, Zhen; Ji, Zheyan; Yu, Jinna (Frontiers in Environmental Science, 2024)
Digital economy is being closely integrated with agricultural development and tapping into its unique potential to alleviate agriculture's carbon emissions (CEs). To explore the mechanism of how digital economy reduce the agricultural carbon emissions, this paper constructs a systematic evaluation method with extend STIRPAT model andUsing panel data drawn from 29 provinces (or municipalities and autonomous regions) in the Chinese mainland from 2013-2020, this article constructs a systematic evaluation method to estimate digital economy levels in rural area while empirically evaluating the influence mechanism of the rural digital economy on agricultural CEs. The results showmain conclusion is that the development of the rural digital economy has a significant negative influence on agricultural CEs, and this result is still valid given robustness tests. Second, Tthe alleviation of CEs based on the rural digital economy is more significant in the higher technological investment zones than that in the lower technological investment zones, and the central and eastern regions also have more significant CEs reduction effect of rural digital economy. Third, the influence mechanism analysis shows thatIn addition, agricultural green technology change is an effective means to promote the rural digital economy's CEs reduction effect. This paper not only provide new empirical evidence for understanding nexus between digital economy and agricultural carbon reduction, but also give constructive policy implication to improve agricultural green development.Hence, some constructive policy implications are reached: (1) the need to build a complete and advanced rural digital economic infrastructure, speed up rural information interconnection and sharing, and construct a unified agricultural and rural data platform; (2) increase financial input to the regions of western and northeastern China, strengthen regional cooperation and improve the coordination of agricultural digital economy development between different regions; (3) Increase input into science research and technology practices while encouraging research and innovation in agricultural green transformation and development.